PENGALAMAN KOMUNIKASI PENGANUT HARE KRISHNA SEBAGAI VEGETARIAN DI PROVINSI BALI - Meria Octavianti; Kismiyati El Karimah; Viswa Pujita Devi (Interaksi: Jurnal Ilmu Komunikasi, 2022)
Hare Krishna is a teaching that focuses on the spiritual aspects of humans originating from India. A Hare Krishna follower must follow the rules to become a vegetarian. This study aims to reveal the communication experience of adherents of Hare Krishna teachings who are vegetarians in the province of Bali. Adherents of Hare Krishna teachings in Bali are the focus of this research because Hare Krishna teachings are growing very rapidly in Bali Province. Based on this, this research was conducted using a qualitative method with a phenomenological approach. Phenomenology was chosen because the communication experience that is the purpose of this research can be revealed not only from the physical experience that is visible but also the spiritual experience experienced by Hare Krishna adherents when they live their lives as vegetarians. The results showed that the communication experience of Hare Krishna adherents with other people who came from outside the adherents was in the form of verbal jokes, debates between believers in Bali, adaptation to Balinese culture, and efforts to spread the teachings of Hare Krishna in Bali.